1997
DOI: 10.1073/pnas.94.22.11819
|View full text |Cite
|
Sign up to set email alerts
|

Glu-tRNA Gln amidotransferase: A novel heterotrimeric enzyme required for correct decoding of glutamine codons during translation

Abstract: The three genes, gatC, gatA, and gatB, which constitute the transcriptional unit of the Bacillus subtilis glutamyl-tRNA Gln amidotransferase have been cloned. Expression of this transcriptional unit results in the production of a heterotrimeric protein that has been purified to homogeneity. The enzyme furnishes a means for formation of correctly charged Gln-tRNA Gln through the transamidation of misacylated Glu-tRNA Gln , functionally replacing the lack of glutaminyl-tRNA synthetase activity in Gram-positive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
310
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(328 citation statements)
references
References 29 publications
(32 reference statements)
3
310
1
Order By: Relevance
“…In other bacteria, archaea, and some organelles however, AspRS is a non-canonical, non-discriminating enzyme (ND-AspRS) that generates both AsptRNA Asp and the misacylated Asp-tRNA Asn (5)(6)(7)12,3,14). This Asp-tRNA Asn is converted to Asn-tRNA Asn by a glutamine-dependent Asp-tRNA Asn /Glu-tRNA Gln amidotransferase (Asp/ Glu-Adt) (26,27,9,28,12). ND-AspRS is most commonly found in organisms lacking asparaginyl-tRNA synthetase (AsnRS) and in these cases, the combination of ND-AspRS and Asp/Glu-Adt provides the sole route for Asn-tRNA Asn biosynthesis and, in some cases, for asparagine biosynthesis as well (7,29).…”
Section: Introductionmentioning
confidence: 99%
“…In other bacteria, archaea, and some organelles however, AspRS is a non-canonical, non-discriminating enzyme (ND-AspRS) that generates both AsptRNA Asp and the misacylated Asp-tRNA Asn (5)(6)(7)12,3,14). This Asp-tRNA Asn is converted to Asn-tRNA Asn by a glutamine-dependent Asp-tRNA Asn /Glu-tRNA Gln amidotransferase (Asp/ Glu-Adt) (26,27,9,28,12). ND-AspRS is most commonly found in organisms lacking asparaginyl-tRNA synthetase (AsnRS) and in these cases, the combination of ND-AspRS and Asp/Glu-Adt provides the sole route for Asn-tRNA Asn biosynthesis and, in some cases, for asparagine biosynthesis as well (7,29).…”
Section: Introductionmentioning
confidence: 99%
“…These coupled glutaminases, termed glutamine amidotransferase (GAT) domains, have been classified as members of the triad-type or the N-terminal nucleophile-type superfamilies (14). More recently, a superfamily of aminoacyltRNA trans-amidases were described as a third unrelated type of GAT (15). Here we show that a domain related to nitrilase (16) containing a conserved Glu-Lys-Cys catalytic triad (16) is the long sought GAT domain for eukaryotic NAD ϩ synthetase, Qns1 (Q for glutamine-dependent, NAD ϩ synthetase).…”
mentioning
confidence: 99%
“…Both genomes encode 36 transfer RNA species, each mapping to the same relative location. Neither strain contains Asn or Gln tRNA species; however, we have identi®ed homologues for the Bacillus subtilis gatABC genes (gene JHP769/HP0830, JHP603/HP0658 and JHP909/HP0975; H. pylori J99 genes are numbers attached to the pre®x`JHP'), which amidate glutamate charged tRNAs to make glutamine-charged tRNAs 6 . Such genes are also likely to be responsible for amidation of appropriate aspartatecharged tRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…Close to its C terminus, titin contains a MLCK-like kinase domain. Although sequence similarity of the catalytic domain of titin to that of its invertebrate analogue, the serine/threonine kinase domain of twitchin 6 , has indicated that titin and twitchin may have similar function, the differential localization of the kinase domains 7,8 , their distinct C-terminal regulatory tails 9,10 and the presence of several titin-specific residues in the active site 11 hint at a different function for titin. Twitchin is a Ca 2+ /S100A1-regulated MLCK 12 .…”
mentioning
confidence: 99%